Perbandingan Tepung Talas Alami (Xanthosoma sagittifolium) dan Termodifikasi dengan Metode Autoclaving-Cooling Terhadap Karakteristik Kimia dan Sensoris Kue Lidah Kucing - Nisaul Mufida, Eva; Sri Wiadnyani, Anak Agung Istri; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 4 (2023): Jurnal ITEPA, 2023)
Lidah kucing is a cookies made of flour, egg white, powdered sugar and margarine. This cake have a form like a cat's tongue, thin, lightweight and has a crunchy texture. This study aims to determine the comparison of taro flour and modified taro flour (Xanthosoma sagittifolium) with autoclaving-cooling method on chemical and sensory properties of the lidah kucing cookies. The design used in this study was a completely randomized design (CRD). Comparative treatment of taro flour and modified taro flour with 6 treatment levels: 100:0, 80:20, 60:40, 40:60, 60:40, 80:20, 0:100. All treatments were repeated three times to obtain 18 experimental units. The data obtained were analyzed statistikally using analysis of variance and if there was a significant effect, it would be continued with the Duncan Multiple Range Test (DMRT). The results showed that the comparison of taro flour and modified taro flour in lidah kucing cookies had a significant effect (P<0.05) on water content, ash content, protein content, fat content and carbohydrate content. Comparison of 20% taro flour and 80% modified taro flour had the best characteristic of lidah kucing cookies with the criteria of water content 1.71%, ash content 1.22%, fat content 45.32%, protein content 5.14%, carbohydrate content 45.91%, the color was brown and liked, the aroma liked, the texture was slightly crunchy and liked, the taste was a bit typical of taro and liked and the overall acceptance was liked.